Seasonal Variation and Meta-Analysis of Cestode Parasites in Capra hircus and Ovis Bhrel from Pune, India - Kishor Dhanji Pendharkar (Cutting Edge Research in Biology Vol. 1, 2022)
The cestode parasites are intestinal endoparasites infecting the grazing domesticated animals, they grow anaerobically in the vertebrate host. These parasites get attached to the intestine by their hooked scolex and absorb digested food material from the hosts intestine. The flesh of the highly infected host is below quality standards. Many times, the multiple worms in the intestine absorbs more food of host and therefore the host suffer from malnutrition and diseases like ulcerations, hemorrhage and therefore causing various disorders and diseases to the host. Moneizia and Stilesia are the two common genera of cestodes infecting grazing mammals including sheep and goats. Goats and sheep are very important economically.There is very limited information is available about their study pertaining to population biology, seasonal variations, prevalence, and intensity of infection. This statistical analysis of information by R software adding some valuable observations in the field of population biology.